2022
DOI: 10.1007/s10518-022-01572-z
|View full text |Cite
|
Sign up to set email alerts
|

Response of soil–pile–superstructure–quay wall system to lateral displacement under horizontal and vertical earthquake excitations

Abstract: The excess pore water pressure (EPWP) generated under the combined vertical and horizontal earthquake excitations is generally greater than that under the unidirectional excitation, which may further affect the dynamic response of soil-pile-superstructure-quay wall (SPSQ) system. This study conducted a coupled effective-stress analysis for the response of SPSQ system to liquefaction-induced lateral displacement under horizontal and vertical earthquake excitations. To accurately describe the lateral displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…A generalized plasticity model, named Pastor-Zienkiewicz Mark-Ⅲ (PZ) (Pastor et al, 1990), with some modifications by Cai et al (2002) was adopted for the soils (Xu et al, 2023). Normally, the parameters for the PZ model were calibrated from either laboratory tests (e.g., cyclic triaxial undrained test) or in-situ tests.…”
Section: Constitutive Modeling Of Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…A generalized plasticity model, named Pastor-Zienkiewicz Mark-Ⅲ (PZ) (Pastor et al, 1990), with some modifications by Cai et al (2002) was adopted for the soils (Xu et al, 2023). Normally, the parameters for the PZ model were calibrated from either laboratory tests (e.g., cyclic triaxial undrained test) or in-situ tests.…”
Section: Constitutive Modeling Of Soilsmentioning
confidence: 99%
“…The safety of the soil-pile -bridge system is a primary concern in the engineering practice (Gerolymos et al, 2008;Cubrinovski et al, 2014;Qu et al, 2018a;Qu et al, 2018b;Qu et al, 2019). Liquefaction-induced lateral displacement has caused much damage to the piled abutment of bridges in the past earthquakes, such as the 1991 Costa Rica Earthquake, the 2011 Christchurch earthquake, and the 2011 Great East Japan earthquake (Gerolymos et al, 2008;Cubrinovski et al, 2014; National Institute for Land and Infrastructure Management of Japan, Public Works Research Institute of Japan, 2014; Tazohb et al, 2008;Xu et al, 2023). It is reported that the inclined piles are more effective than vertical piles in restricting lateral displacements of superstructures subjected to liquefaction induced lateral displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in recent decades, many researchers in the field of geotechnical engineering have tried to propose and develop suitable and relatively accurate constitutive models to appropriately show the behavior of soils (see, for example, [1][2][3][4]). On the other hand, one of the situations that may result in the failure of structures is related to dynamic and cyclic loading of soils and the related problems, such as liquefaction observed during earthquakes [5][6][7][8][9][10][11][12][13][14]. Therefore, in addition to precise simulation of the soil behavior under monotonic loadings, a suitable constitutive model for the soil behavior under cyclic loadings is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the variability in the direction of winds, the pile foundations of transmission towers could be subjected to uplift, compression, and horizontal loads. (Xu et al, 2023;Xu et al, 2013;Xu et al, 2017a;Qu et al, 2018b). In the engineering design, the uplift capacity is one of the significant factors to be considered for the pile of transmission towers.…”
Section: Introductionmentioning
confidence: 99%